Disordered eating patterns in coeliac disease: a framework analysis. Issue 6 (17th April 2017) - Satherley, R.‐M.; Higgs, S.; Howard, R.
Abstract: Objective: The need for dietary‐management in coeliac disease may lead to the development of disordered eating patterns. A theoretical model of disordered eating has been proposed to explain disordered eating in coeliac disease. The aim of this study was to explore the experiences of typical and disordered eating in coeliac disease to gain a greater understanding of these processes and explore specific pathways within this model. Methods: We interviewed 21 individuals with coeliac disease, recruited from a previous database, about their experiences with food and food environments. Information about disordered eating status was assessed via questionnaire. The interviews were analysed qualitatively using Framework analysis, which was underpinned by the theoretical model of disordered eating in coeliac disease. Results: Experiences differed between participants scoring high on measures of disordered eating and those who scored low (typical eaters). Participants scoring high on measures of disordered eating were concerned about the consequences of their gluten‐free diet on body image and they described eating patterns similar to binge/restrict cycles. Typical eaters reported being able to integrate their dietary self‐management into their daily lives; however, general concerns around food and cross‐contamination were associated with a restriction in food intake. Conclusions: Coeliac disease has a varied impact on eating patterns. The need to follow a gluten‐free diet and to be vigilant around food has to be balanced with concerns around food availability and cross‐contamination which have the potential to contribute towards disordered eating attitudes and behaviours. The findings suggest that the theoretical model of disordered eating provides an adequate explanation of disordered eating patterns in coeliac disease.